Rapid spread and high mortality due to community-acquired pneumonia caused by Acinetobacter baumannii (CAP-AB) in a Covid-19 intensive care unit - Navid Shafigh; Fatemeh Roodneshin; Elnaz Shafigh; Mahtab Poor Zamany Nejat Kermany; Shadi Ziaie; James Miller; Mohammad Gharehbeglou; Niyoosha Masoumzadeh; Morteza Hasheminik; Jamshid Ordoni Avval (Journal of Family Medicine and Primary Care, 2022)
Acinetobacter baumannii is a rare but dangerous gram-negative bacteria causing nosocomial infections, especially in intensive care units. The increased use of antibiotics in the treatment of bacterial infections leads to drug resistance, delays, or failures in treatment. The patient is a 48-year-old man with coronavirus disease (COVID-19) being treated in the intensive care unit. After contracting Acinetobacter baumannii, the patient's condition deteriorated, and he developed severe pulmonary problems. Due to the unknown presence of Acinetobacter baumannii in the patient, this bacterium transmitted to six other patients in the ward, which resulted in their deaths. In this report, we describe the causes and risk factors of the disease, and the results of laboratory tests and therapeutic processes.